TRANSFORMATION OF ISLAMIC RELIGIOUS EDUCATION LEARNING IN THE DIGITAL ERA: OPPORTUNITIES AND CHALLENGES IN ENHANCING TEACHER AND STUDENT READINES - Gesika Avelina; Muhammad Chairullah Tamiran; Sartia S.A Sanua; Rendy S. Sambara (Adisam Publisher, 2026)
Digital transformation has significantly reshaped various aspects of education, including the teaching and learning of Islamic Religious Education (IRE). Rapid technological advancements require the adaptation of instructional strategies, teaching methods, and learning media to ensure that IRE remains relevant to the needs of students in the digital era. This study aims to analyze the transformation of IRE learning in the digital age by examining the opportunities and challenges associated with enhancing the readiness of teachers and students. The research employs a qualitative descriptive approach using a library research method through the analysis of relevant scholarly literature. The findings indicate that the digitalization of IRE offers opportunities to expand access to Islamic learning resources, enhance teachers' creativity, and increase student engagement through various digital learning platforms and media. Nevertheless, the transformation process also faces several challenges, including limited digital competence among teachers, disparities in technological infrastructure, low levels of digital literacy, and ethical issues related to technology use. Therefore, the successful implementation of digital IRE learning requires the readiness of human resources and the effective integration of technology while maintaining alignment with Islamic values and educational principles.